Effectiveness of Pregnant Woman Class in The Prevention of Pregnancy Anemia in Banyuwangi, East Java - Andriani, Yeni; Respati, Supriyadi Hari; Astirin, Okid Parama (Journal of Maternal and Child Health, 2016)
Background: In developing countries 40% of maternal mortality is associated with pregnancy anemia. Pregnancy anemia has negative effect to mothers, before, during, and after delivery. The purpose of this study was determined effectiveness of pregnant woman class in the prevention of pregnancy anemia in Banyuwangi, East Java.Subjects and Method: This was an analytical observational study with retrospective cohort design. This study was conducted at Benculuk health center, Banyuwangi, East Java. A total of 100 subjects were selected for this study by fixed exposure sampling, consisting of 50 pregnant mothers who participated pregnant woman class and 50 ÃÂ who did not participate pregnant woman class. The dependent variable was pregnancy anemia. The independent variables wereÃÂ  participation in the pregnant woman class, maternal education, family income, food myth, and visit to obstetric gynecology specialist. Anemia was measured by spectrophotometer. Other variables were measured by a set of questionnaire. The data were analyze by multiple logistic regression.Results: Participation in pregnant woman class (OR=0.18; CI 95%= 0.03 to 1.21; p=0.078), maternal education Ã¢â°Â¥ senior high school (OR=0.07; CI 95%= 0.01 to 0.92; p=0.043), and high family income (Ã¢â°Â¥ Rp 1,599,000) (OR=0.18; CI 95%= 0.31 to 1.03; p=0.054) decreased the risk of pregnancy anemia. Myth in food restriction (OR=4.47; CI 95%=0.73 to 27.51; p=0.106) increased the risk of pregnancy anemia. There was no relationship between visit to obstetric and gynecology specialist and the risk of pregnancy anemia (OR=0.93; CI 95%=0.09 to 9.17; p=0.952).Conclusion: Participation in pregnant mother class, maternal education Ã¢â°Â¥ senior high school, and high family income (Ã¢â°Â¥ Rp 1,599,000) decrease the risk of pregnancy anemia. Myth in food restriction increase the risk of pregnancy anemia. There is no relationship between visit to obstetric and gynecology specialist and the risk of pregnancy anemia.Keywords: pregnant woman class, pregnancy anemiaCorrespondence:ÃÂ Yeni Andriani. Masters Program in Public Health, Sebelas Maret University, Surakarta.Journal of Maternal and Child Health 2016, 1(4): 230-241https://doi.org/10.26911/thejmch.2016.01.04.04